2021
DOI: 10.1371/journal.pone.0257611
|View full text |Cite
|
Sign up to set email alerts
|

Socio-spatial cognition in cats: Mentally mapping owner’s location from voice

Abstract: Many animals probably hold mental representations about the whereabouts of others; this is a form of socio-spatial cognition. We tested whether cats mentally map the spatial position of their owner or a familiar cat to the source of the owner’s or familiar cat’s vocalization. In Experiment 1, we placed one speaker outside a familiar room (speaker 1) and another (speaker 2) inside the room, as far as possible from speaker 1, then we left the subject alone in the room. In the habituation phase, the cat heard its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Another explanation for the correlation between gaze and vocalizations in dogs, but not cats, is that vocalizations are not gaze-triggers for cats. One study suggests that cats use their sense of hearing to represent where individuals are around them (Takagi et al, 2021). Thus, cats may take vocalizations as primarily informative compared to social, whereas dogs may find vocalizations from owners more inviting for interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the correlation between gaze and vocalizations in dogs, but not cats, is that vocalizations are not gaze-triggers for cats. One study suggests that cats use their sense of hearing to represent where individuals are around them (Takagi et al, 2021). Thus, cats may take vocalizations as primarily informative compared to social, whereas dogs may find vocalizations from owners more inviting for interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Cats are also able to follow human gaze as referential signal (Pongrácz et al, 2019). Performance of cats has recently also been tested in other cognitive tasks, for example they have been shown to be able to differentiate between different quantities (Pisa & Agrillo, 2009), they are able to mentally represent non-visible objects (Takagi et al, 2021) and they imitate human action to solve a task (Fugazza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Performance of cats has recently also been tested in other cognitive tasks. For example they have been shown to differentiate between different quantities (Pisa & Agrillo, 2009), they are able to mentally represent the location of non-visible objects (Takagi et al, 2021) and reproduce a human's familiar action on an object (touch it with hand/paw or face) (Fugazza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Relying upon vocal cues, cats can discriminate their owner from a stranger (Saito & Shinozuka 2013) and speech specifically addressed to them from speech addressed to human adults (de Mouzon et al under review). Cats can predict their owner's face and mentally map their owner's location upon hearing their voice, suggesting cross-modal mental representation of at least one human (Takagi et al 2019(Takagi et al , 2021. Using a cross-modal paradigm, Quaranta et al (2020) reported that, just like dogs (Albuquerque et al 2015) and horses (Trösch et al 2019), cats can integrate visual and auditory signals to recognize human's emotion, and even appear to modulate their behaviour according to the valence of the emotion perceived.…”
Section: Introductionmentioning
confidence: 99%